VD_FINDINFO HC / 2025 / 702 vom 11. November 2025 - VD Tribunal cantonal (2025)
JUGEMENT PAR DÉFAUT, CONSTATATION DES FAITS, DÉBAT DU TRIBUNAL | 148 CPC (CH), 150 al. 1 CPC (CH), 223 al. 1 CPC (CH), 223 al. 2 CPC (CH), 228 al. 1 CPC (CH), 228 al. 2 CPC (CH), 234 al. 1 CPC (CH), 234 al. 2 CPC (CH)